2019
DOI: 10.1177/0023830919828201
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Gaydar: Perception of Sexual Orientation Based on Female Voice

Abstract: We investigated auditory gaydar (i.e., the ability to recognize sexual orientation) in female speakers, addressing three related issues: whether auditory gaydar is (1) accurate, (2) language-dependent (i.e., occurs only in some languages, but not in others), and (3) ingroup-specific (i.e., occurs only when listeners judge speakers of their own language, but not when they judge foreign language speakers). In three experiments, we asked Italian, Portuguese, and German participants (total N = 466) to listen to vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 55 publications
(111 reference statements)
0
7
0
1
Order By: Relevance
“…Gay and lesbian individuals are targets of stereotyping and stigmatization, even when their SO is not explicitly disclosed but "detected" by others from minimal cues such as voice (Fasoli et al, 2016). An increasing body of research has shown that listeners categorize speakers' SO according to how they sound (Gaudio, 1994;Linville, 1998;Smyth, Jacobs, & Rogers, 2003;Munson, 2007), even when they speak a foreign language (Sulpizio et al, 2015;Sulpizio, Fasoli, F., Antonio, R., Eyssel, F., Paladino, M. P., & Diehl, 2019), talk for a few seconds (Mack & Munson, 2012), or utter meaningless syllables rather than conveying a meaningful message (Tracy, Bainter, & Satariano, 2015). Sometimes this categorization process happens to be accurate, whereas at other times, it occurs on the basis of stereotypical ideas of how gay men and lesbian women are believed to sound (for an overview see Fasoli et al, 2016;Rule, 2017).…”
Section: Sexual Orientation and Gender Stereotypesmentioning
confidence: 99%
“…Gay and lesbian individuals are targets of stereotyping and stigmatization, even when their SO is not explicitly disclosed but "detected" by others from minimal cues such as voice (Fasoli et al, 2016). An increasing body of research has shown that listeners categorize speakers' SO according to how they sound (Gaudio, 1994;Linville, 1998;Smyth, Jacobs, & Rogers, 2003;Munson, 2007), even when they speak a foreign language (Sulpizio et al, 2015;Sulpizio, Fasoli, F., Antonio, R., Eyssel, F., Paladino, M. P., & Diehl, 2019), talk for a few seconds (Mack & Munson, 2012), or utter meaningless syllables rather than conveying a meaningful message (Tracy, Bainter, & Satariano, 2015). Sometimes this categorization process happens to be accurate, whereas at other times, it occurs on the basis of stereotypical ideas of how gay men and lesbian women are believed to sound (for an overview see Fasoli et al, 2016;Rule, 2017).…”
Section: Sexual Orientation and Gender Stereotypesmentioning
confidence: 99%
“…By referring to targets’ everyday appearances, straight categorization bias should have been reduced because the likelihood of introducing gendered fashions is increased (Lick & Johnson, 2016). Analogous to previous research (Kachel et al, 2018; Sulpizio et al, 2015, 2019), vocal stimuli in our study consisted of recordings of the same single read sentence for every target. In contrast to the visual stimuli, this possibly left too little space for interindividual differences (vs. 20-second excerpt of a read text used by Valentova & Havlíček, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…We did not adopt this commonly used procedure but made straightness the effect to be explained (Bruckmüller, 2013). By doing so, we accounted for studies showing more straight than lesbian/gay targets to be accurately perceived (Lick & Johnson, 2016; Sulpizio et al, 2015; Sulpizio et al, 2019) and for studies showing that people are categorized as straight or nonstraight (Ding & Rule, 2012; Lick, Johnson, & Rule, 2015). Nevertheless, our findings are comparable to previous ones because the total numbers of lesbian/gay and straight stimuli were the same.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations